How Do Friends and Strangers Play the Game Taboo? A Study of Accuracy, Efficiency, Motivation, and the Use of Shared Knowledge. (September 2018) - Pollmann, Monique M. H.; Krahmer, Emiel J.
According to common belief, friends communicate more accurately and efficiently than strangers, because they can use uniquely shared knowledge and common knowledge to explain things to each other, while strangers are restricted to common knowledge. To test this belief, we asked friends and strangers to play, via e-mail and face-to-face, the word-description game Taboo, in which objects need to be described without using certain "taboo" words. When descriptions were sent via e-mail, there was no difference in accuracy (number of correct answers) nor in efficiency (number of words per correct answer) between friends and strangers. When descriptions were given face-to-face, friends were more accurate than strangers, but not more efficient (number of seconds and words per correct answer). Shared knowledge did not predict accuracy or efficiency. Hence, our findings do not support the idea that friends only need a few words to understand each other.